Pengaruh Kualitas Layanan Terhadap Kepuasan Karyawan pada Bagian Laundry PT. KSO GDSK-PDI (KGP) Kabupaten Teluk Bintuni - Helda Yohanesia; Fensca F Lahallo; Rais Rumaday; Ino Rocky (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the effect of service quality on employee satisfaction in the laundry division of PT. KSO GDSK-PDI (KGP), Teluk Bintuni Regency. The research employed a quantitative approach using a simple linear regression analysis. Data were collected through questionnaires distributed to 93 respondents selected using simple random sampling. The results indicate that service quality has a positive and significant effect on employee satisfaction. The regression equation obtained is Y = 0.400 + 0.967X, indicating that every one-unit increase in service quality increases employee satisfaction by 0.967 units. The t-test result shows a significance value of 0.000 (<0.05) with a t-value of 14.341, confirming that service quality significantly affects employee satisfaction. Furthermore, the coefficient of determination (R²) is 0.693, meaning that service quality explains 69.3% of the variation in employee satisfaction, while the remaining 30.7% is influenced by other variables not examined in this study. Therefore, improving service quality is essential for increasing employee satisfaction within the company.